From Rural Abangan to Urban Santri: Social and Physical Transformation of Kampung Krapyak, Yogyakarta 1910-1980s - Izul Adib; Pulung Sumantri (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
This article describes the social and physical transformation of Kampung Krapyak in Yogyakarta, which started from a rural village based on an abangan group moving to an urban village dominated by santri groups. This study aimed to determine the history and development of Krapyak from the 1910s to the 1980s. The method used in this paper is a historical method that includes heuristics, verification, interpretation, and historiography. This paper’s focus explicitly discusses the social and physical changes of Kampung Krapyak from the original village with an agrarian culture on the outskirts of the city to being an urban santri village with a strong Islamic identity. The existence of the Pesantren Krapyak since 1910 has succeeded in making significant changes to Kampung Krapyak, making Krapyak known as one of the centers of Islamic religious education in Yogyakarta in the 1980s.